Penatalaksanaan Holistik Pada Wanita Usia 50 Tahun dengan Gout Arthritis Melalui Pendekatan Kedokteran Keluarga - Maryanto, Erlicha Paramitha; Karyus, Aila (Medula, 2024)
Gout arthritis is a progressive disease due to the deposition of monosodium urate crystals in joints, kidneys, and other connective tissues due to chronic hyperuricemia. This disease needs to be managed comprehensively so that patients must know about their disease and have awareness and can make lifestyle modifications so that treatment goals can be achieved, prevent complications that may occur, and improve the patient's quality of life. This can be realized with family medicine-based management. The aim of this study is to identify internal, external risk factors and clinical problems found in patients, apply a holistic and comprehensive family doctor approach according to the problems found in patients, and carry out evidence-based medicine management that is family-approach, patient-centered and community oriented. The study is a case report. Primary data were obtained through history taking, physical examination and home visits. Secondary data were obtained from the patient's medical record. A 50-year-old female patient came with complaints of pain in the both knees. The patient has been diagnosed with uncontrolled gout since 2 months ago. In the knowledge assessment, the initial score before the intervention was 5 (low) and after the intervention it was 9 (high). In the aspect of uric acid levels there is a decrease in uric acid levels from 9,3 mg/dL to 5,6 mg/dL. In the aspect of diet there is a change in the type of food that is appropriate. In the aspect of physical activity there is a change in physical activity of 30 minutes of exercise per day. Enforcement of diagnosis and management of these patients has been done holistically, patient centered, family approach and community oriented based on several theories and the latest research. In the process of behavior change, the patient has reached the trial stage.